Glial solute carrier transporters in drosophila and mice. - Featherstone, D.E. (Glia, 2011)
Glia regulate brain physiology primarily by regulating the movement and concentration of substances in the extracellular fluid. Therefore, one approach to understanding the role of glia in brain physiology is to study what happens when glial transporters are removed or modified. The largest and most highly conserved class of transporter is solute carrier (SLC) proteins. SLC proteins are highly expressed in brain, and many are found in glia. The function of many SLC proteins in the brain--particularly in glia--is very poorly understood. SLC proteins can be relatively easily knocked out or modified in genetic model organisms to better understand glial function. Drosophila are popular genetic model organisms that offer a nice balance between genetic malleability and brain complexity. They are ideal for such an endeavor. This article lists and discusses SLC transporter family members that are expressed in both mouse and Drosophila glia, in an effort to provide a foundation for studies of glial SLC transporters using Drosophila as a model.